Spindle cell oncocytoma of the pituitary tumor: A rare case report and literature reviews - Chang, Chia Ning; Shen, Chiung Chyi (Frontiers in Surgery, 2023)
Spindle cell oncocytoma of the pituitary gland is increasingly established with improvement in histological and immunohistochemical examination. However, the diagnosis was often mistaken under images studies and nonspecific clinical manifestation. We provide this case to overview of the characters of the rare tumor and to demonstrate challenges of diagnosis and current treatments.